Pahilot: The Faith Healing Tradition of the Ati–Atihan Festival - Mujal, Rhuda Malacad (The PASCHR journal, 2020)
This study focuses on Pahilot—the faith healing tradition of the Ati- Atihan Festival in Kalibo, Aklan, in the island of Panay. The researcher uses oral history in data gathering validated by library researches. Historical events with their popular beliefs and myths are analyzed. The important finding establishes that Pahilot, as a tradition bears a deep religious significance in the celebration of the Ati-Atihan festival where a priest rubs the image of the Sto. Nino in the devotees body. The study recommends that the people of Panay should practice this kind of tradition because it signifies their history, religion and culture.